Newborn Screening for Severe Combined Immunodeficiency-A History of the TREC Assay - Mary T. Bausch-Jurken; James W. Verbsky; John M. Routes (MDPI AG, 2017)
Infants born with T cell lymphopenias, especially severe combined immunodeficiency (SCID) are at risk for serious, often fatal infections without intervention within the first year or two of life. The majority of these disorders can be detected through the use of the T cell recombination excision circle assay (TREC assay.) The TREC assay detects the presence of non-replicating, episomal DNA that is formed during T cell development. This assay initially developed to measure thymic output during aging and HIV infection, has undergone modifications for the purpose of newborn screening (NBS) for SCID. To meet the requirements for inclusion on NBS panels, the assay needed to utilize blood from dried blood spots on NBS cards, and be both sensitive and specific, avoiding the costs of false positives. Currently, the assay relies upon real time, quantitative PCR (RT-qPCR) to detect TRECs in punches taken from dried blood spots. This review seeks to highlight some of the early work leading up to the initial implementation of the TREC assay for SCID detection, and the subsequent revisions made to optimize the assay.